Improved Depression Symptoms Among Low-Income Mexican Americans Participating in a Community-Clinical Diabetes Intervention - MinJae Lee; Joseph H. Conroy; Zihan Yang; Sein Lee; Paul G. Yeh; Juliana Z. Lopez; Natalia I. Heredia; Lisa A. Mitchell-Bennett; Maribel Sifuentes; Belinda M. Reininger (Journal of Primary Care & Community Health)
Background: Adults with type 2 diabetes mellitus and comorbid depression face complex disease management. Salud y Vida, a diabetes management intervention for Mexican Americans in the Rio Grande Valley of Texas, may mitigate depression through social support and community-clinic referrals. Methods: In a cohort study, 292 Salud y Vida participants completed the patient health questionnaire (PHQ-9) at baseline, month 6, and month 12. A PHQ-9 score of ≥5 indicated mild depression and activated a mental health referral. Using SAS 9.4 with significance set at <.05, we conducted multivariable longitudinal negative binomial regression to assess changes in depression level. Results: The proportion of participants with a PHQ-9 ≥5 decreased from 36% at baseline to 18% in month 6 (adjusted risk ratio = 0.51, 95% CI = 0.41-0.62; P  < .001). Among those with clinical depression at baseline (n = 121), mean PHQ-9 scores dropped 45% by month 6 (9.60-5.28; adjusted rate ratio = 0.55; 95% CI = 0.47, 0.65, P  < .001) and an additional 22% by month 12 (5.28-4.10; adjusted rate ratio = 0.78; 95% CI = 0.66, 0.91; P  < .002). Conclusion: Salud y Vida participation is correlated with significant depression symptom improvements in Mexican American adults with diabetes and comorbid depression, demonstrating that chronic care management interventions can address multiple chronic conditions.